Describing the readiness for interprofessional education among university students attending healthcare programs: insights from a monocentric cross-sectional study - Spada, Florian; Caruso, Rosario; Notarnicola, Ippolito; De Maria, Maddalena; Duka, Blerina; Arapi, Alta; Prendi, Emanuela; Rocco, Gennaro; Stievano, Alessandro (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Readiness for interprofessional education (IPE) was recognized by international authorities as a key approach for educating students attending healthcare programs. Thus far, there are no descriptions of readiness for IPE in the Albanian context. For this reason, this study aimed to describe readiness for IPE, assessed by measuring "teamwork and collaboration" and "positive professional identity, roles, and responsibilities" among students attending healthcare programs in an Italian-speaking university based in Albania, and describe the correlations between readiness for IPE and the characteristics of the respondents.Methods: This study had a descriptive observational design, a cross-sectional data collection, and a convenience sampling procedure performed in a single centre. The study was accomplished between April 2020 and June 2021, involving 688 students, 38.2% of the entire population of students attending healthcare programs in the context of the investigation.Results: The teamwork and collaboration mean score was 4.40 (standard deviation = 0.56), and no differences were found between programs (p-value=0.159). The positive professional identity, roles, and responsibilities mean score was 4.33 (standard deviation = 0.64) with no differences between programs (p-value=0.340). Females attending nursing or midwifery reported higher positive professional identity, roles, and responsibilities scores (p-value=0.020), and females in dentistry reported higher teamwork and collaboration scores than males (p-value=0.045).Conclusions: Future research should evaluate readiness for IPE longitudinally to ascertain its trajectories over time and analyze any potential individual- or organizational-level variables that may impact IPE and sex-related differences regarding factors influencing IPE.